Transcriptional Activation of Matricellular Protein Spondin2 (SPON2) by BRG1 in Vascular Endothelial Cells Promotes Macrophage Chemotaxis - Li, Nan; Liu, Shuai; Zhang, Yuanyuan; Yu, Liming; Hu, Yanjiang; Wu, Teng; Fang, Mingming; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
The matricellular protein SPON2 plays diverse roles in the development of cardiovascular diseases. SPON2 is expressed in endothelial cells, but its transcription regulation in the context of atherogenesis remains incompletely appreciated. Here we report that SPON2 expression was up-regulated by pro-atherogenic stimuli (oxLDL and TNF-a) in vascular endothelia cells. In addition, endothelial SPON2 was elevated in Apoe-/-mice fed on a Western diet compared to the control mice. Induction of SPON2 in endothelial cells by pro-atherogenic stimuli was mediated by BRG1, a chromatin remodeling protein, both in vitro and in vivo. Further analysis revealed that BRG1 interacted with the sequence-specific transcription factor Egr-1 to activate SPON2 transcription. BRG1 contributed to SPON2 trans-activation by modulating chromatin structure surrounding the SPON2 promoter. Functionally, activation of SPON2 transcription by the Egr-1/BRG1 complex provided chemoattractive cues for macrophage trafficking. SPON2 depletion abrogated the ability of BRG1 or Egr-1 to stimulate endothelial derived chemoattractive cue for macrophage migration. On the contrary, recombinant SPON2 rescued endothelial chemo-attractability in the absence of BRG1 or Egr-1. In conclusion, our data have identified a novel transcriptional cascade in endothelial cells that may potentially promote macrophage recruitment and vascular inflammation leading to atherogenesis.